The Cohesion in Keynote Address on Thai Language and Literature by Prime Ministers of Thailand - Tonpradit, Rungroj; Kamolsujja, Wichetchay; Sriyabhaya, Warawat (Chophayom Journal, 2021)
This study aims to analyze the cohesion in keynote address on Thai language and literature by prime ministers of Thailand. Three speeches from three different prime ministers were collected and analyzed, based on the cohesion concept. The result shows 6 types of cohesion used; reference, repetition, ellipsis, replacement, lexical, and conjunction. There were 17 types of conjunctions found the most, for example; reformulatary relation, additive relation, and emphasis relation. Lexicon cohesion was found only in Prime Minister Chuan Leekhai’s speech. For language identity coherence, it was found that Prime Minister H.R Kukrit Pramoj used the most formal language because it was a speech address in front of the King’s throne-hall, besides Prime Minister Prem Tinsulanonda used a euphemism with conjunction the most because the speech was well-drafted. Also, Prime Minister Chuan Leekpai’s speech used additive relation to explain some examples related to the local dialect. Keywords: Cohesion, Keynote Address, Prime Minister of Thailan